Antioxidant Potency of Red Dragon Fruit Flesh and Peel Prepared by Different Methods - Febrianti, Novi; Purbosari, Purwanti P.; Hertiani, Triana; Moeljopawiro, Sukarti; Haryana, Sofia M. (Current Nutrition & Food Science, 2020)
Background: Red dragon fruit (Hylocereus polyrhizus, (F.A.C. Weber) Britton & Rose) is widely consumed all over the world nowadays. The peel and flesh of red dragon fruit contain many bioactive compounds with high antioxidant activity. The preparation process is critical to maximizing the yield of the antioxidant content. Objective: The objectives of this research were to evaluate total phenolic content (TPC), total flavonoid content (TFC), as well as the antioxidant activity of peel and flesh of red dragon fruit prepared by various methods. Methods: The fresh and dried samples of peel and flesh of red dragon fruit were prepared via maceration and non-maceration process. Ethanol (96%) was used as the solvent in maceration. In the nonmaceration process, the samples were ground using a blender and pressed using a juicer. TPC was analyzed by Folin-Ciocalteau methods, while TFC was determined by spectrophotometry UV-Vis with AlCl3. Antioxidant activity was analyzed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and β-carotene bleaching (BCB) tests. Results: TPC from all of the measured samples varied from 22.43 ± 0.27 to 80.54 ± 0.43 mg GAE/g dry extract. The highest TPC concentration was found in the blended peel via maceration and the lowest concentration was found in the blended flesh without maceration. The dried peel via maceration treatment had the highest TFC (51.96 ± 0.084 mg of QE/g dry extract). Regarding to the antioxidant activity, the blended flesh ethanolic extract and blended peel ethanolic extract had the highest DPPH radical scavenging, IC50=966.83 ± 11.62 and 973.81 ± 3.571ppm, respectively. While the blended peel ethanolic extract had the highest BCB antioxidant activity (IC50= 45.48 ± 6,79 mg/mL). Conclusion: Preparation methods affect the antioxidant activity of red dragon fruit peel and flesh. The highest TPC and antioxidant activity (BCB test) can be found in the ethanolic extract of the blended peel. The highest TFC can be found in the ethanolic extract of dried-peel. Both the ethanolic extracts, blended peel and blended flesh, had the same DPPH radical scavenging activity.
Keywords: natural health